2016
DOI: 10.1159/000446915
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Central Adiposity and Autonomic Dysfunction in Obesity

Abstract: Objective: To determine the relationship between central adiposity parameters and autonomic nervous system (ANS) dysfunction. Subjects and Methods: The study included 114 obese individuals without any cardiovascular risk factors. Weight (in kg), height (in m), and waist circumference (WC; in cm) were measured and body mass index was calculated. Echocardiographic examination was performed to measure left ventricular mass and epicardial fat thickness (EFT). All the participants underwent an exercise test and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
0
25
2
2
Order By: Relevance
“…Data from human studies as well as animal models have suggested that obesity leads to alterations in autonomic regulation, particularly an increase in sympathetic nerve activity to various tissues [3]. Indeed, obesity-induced hypertension has been linked to increased sympathetic outflow to the kidney, which leads to increased fluid retention and vasoconstriction, as well as activation of the renin-angiotensin system; together, these promote an increase in arterial pressure [4].…”
Section: Introductionmentioning
confidence: 99%
“…Data from human studies as well as animal models have suggested that obesity leads to alterations in autonomic regulation, particularly an increase in sympathetic nerve activity to various tissues [3]. Indeed, obesity-induced hypertension has been linked to increased sympathetic outflow to the kidney, which leads to increased fluid retention and vasoconstriction, as well as activation of the renin-angiotensin system; together, these promote an increase in arterial pressure [4].…”
Section: Introductionmentioning
confidence: 99%
“…I read the paper by Fidan-Yaylali et al [ 1 ] entitled “The Association between Central Adiposity and Autonomic Dysfunction in Obesity” with great interest. The authors reported that indices of heart rate recovery, especially those at the late decay phase, as predictors of cardiac autonomic dysfunction are impaired in obese individuals.…”
mentioning
confidence: 99%
“…Cardiac autonomic dysfunction is described as a dysregulation of cardiovascular autonomic function without any other reason, inducing dysautonomia, and is accepted as an independent prognostic factor for cardiovascular morbidity and mortality [ 2 ]. Cardiovascular autonomic reflex tests (CARTs), heart rate variability (HRV), heart rate turbulence, and heart rate recovery can be used for the evaluation of cardiac autonomic dysfunction [ 1 , 3 ].…”
mentioning
confidence: 99%
“…Strikingly, obesity is associated with cardiometabolic dysfunction even in children, with increasing body mass index correlating with higher systolic blood pressure, total cholesterol levels, and fasting blood glucose in obese [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] year olds [13]. Consistent with this, a large study of 2.3 million Israeli adolescents has recently shown that childhood obesity and even elevated body mass index within the normal range correlates with increased risk of cardiovascular-related death in adulthood [14].…”
Section: Obesity and Hypertensionmentioning
confidence: 99%
“…While peripheral mechanisms including chronic inflammation, physical compression of the kidneys, and vascular dysfunction have been proposed as potential mediators of obesity-associated hypertension, there has been substantial evidence supporting a critical role for the central nervous system in driving this linkage. Data from human studies as well as animal models have suggested that obesity leads to alterations in autonomic regulation, particularly an increase in sympathetic nerve activity to various tissues [3]. Indeed, obesity-induced hypertension has been linked to increased sympathetic outflow to the kidney, which leads to increased fluid retention and vasoconstriction, as well as activation of the renin-angiotensin system; together, these promote an increase in arterial pressure [4].…”
Section: Introductionmentioning
confidence: 99%